ERGONOMIC ANALYSIS FOR WORKERS OF BACKHOES AND WHEEL LOADERS (Fiep Bulletin - online, 2014)
In the ergonomic analysis of jobs tied to construction, there is a need for adjustment of some jobs to the employees involved; therefore, the present study aims to identify inadequacies in the field of ergonomics, based on the use of the Questionnaire Nordic workplace characteristic operators for excavator and loader. The questionnaire aims painful body regions than five workers to every outfit. Analysis Nordic questionnaire, it can be concluded that the index is pain in the wrists/hands and back, these problems can be corrected by the worker's awareness, as well as adjusting the steering wheel, the angle of inclination and height bank.
Keywords: Ergonomics; Civil Engineering; Nordic Questionnaire